Characterization of YIG nanopowders by mechanochemical synthesis - (:unkn) unknown (ELSEVIER SCIENCE SA, 2009)
Yittrium iron garnet, Y(3)Fe(5)O(12) (YIG), is a material used widely in electronic devices for the microwave region as well as the magnetic bubble domain-type memories. Yittrium iron garnet (Y(3)Fe(5)O(12)) was produced by mechanochernical synthesis from Y(2)O(3) and Fe(2)O(3) with a particle size of around 150 nm. Dense ceramics with theoretical density of around 95% was obtained from mechanochemically activated powders after sintering at 1425 degrees C for 10 h without calcination step. Ferro-magnetic resonance (FMR) spectrum and microwave absorption spectrum of the YIG nanoparticles were studied at different frequencies and magnetic fields. The signal exhibits a resonance character at each frequency. It was observed that the location of the FMR signal peak at the field axes monotonically shifts to higher field with increasing frequency. The dielectric properties of YIG pellets produced from nanopowder was studied over a wide range of frequency and as a function of temperature. It was observed that the dielectric constant, dielectric loss and electrical conductivity gradually increase with temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Yittrium iron garnet; Y(3)Fe(5)O(12) (YIG); Dielectric properties; Magnetic properties; MAGNETIC-PROPERTIES; MAGNETOOPTICAL PROPERTIES